Examination of lower-upper limb of power and force parameters of elite athletes - Aktas, S.; Cakmakci, O. (Physical Education of Students, 2020)
Background and Study Aim. In this study, it is aimed to evaluate the power and force parameters of lower and upper extremities of the individual and team athletes who practice different branches. Material and Methods. 32 elite athletes, most of whom are university students, with an average age of 21.16 ± 2.08, who are active in sports, participated in the study. The groups were formed from Boxing and Handball (BG and HG) branches in which the upper extremities are used predominantly and from Taekwondo and Football (TG and FG) branches in which the lower extremities are used predominantly. The anaerobic power values of each individual`s upper and lower extremities were measured by a Monark 894E. The isokinetic force values of dominant arms and legs were measured by a Cybex humac norm device. Results. After examination of the data it was found that the upper extremity power values of BG and HG were significantly higher than TG when the top values of peak powers (PP) were evaluated. In the evaluations with respect to leg 60°/s and 180°/s extension and flexion; HG and FG was significantly higher than TG in 60°/s extension at PP; HG and FG were significantly indifferent but they were significantly higher than BG and TG in 60°/s flexion at PP. In the comparisons of the groups` 60°/s and 180°/s extension and flexion values of lower extremities anaerobic power and isokinetic force and lower extremities` wingate values, a number of positive relations were found between all of the groups. All of the groups were positively related to each other in terms of upper extremities wingate and 60°/s, 180°/s internal and external isokinetic forces. Conclusions. Both the isokinetic arm force values and arm wingate levels were higher in the branches in which the upper extremities are used predominantly than the branches in which the lower extremities are used predominantly. On the other hand, the difference seen in the upper extremities was not seen in the lower extremities.